EhRacM differentially regulates macropinocytosis and motility in the enteric protozoan parasite Entamoeba histolytica. - Misato Shimoyama; Kumiko Nakada-Tsukui; Tomoyoshi Nozaki (PLoS Pathogens)
Macropinocytosis is an evolutionarily conserved endocytic process that plays a vital role in internalizing extracellular fluids and particles in cells. This non-selective endocytic pathway is crucial for various physiological functions such as nutrient uptake, sensing, signaling, antigen presentation, and cell migration. While macropinocytosis has been extensively studied in macrophages and cancer cells, the molecular mechanisms of macropinocytosis in pathogens are less understood. It has been known that Entamoeba histolytica, the causative agent of amebiasis, exploits macropinocytosis for survival and pathogenesis. Since macropinocytosis is initiated by actin polymerization, leading to the formation of membrane ruffles and the subsequent trapping of solutes in macropinosomes, actin cytoskeleton regulation is crucial. Thus, this study focuses on unraveling the role of well-conserved actin cytoskeleton regulators, Rho small GTPase family proteins, in macropinocytosis in E. histolytica. Through gene silencing of highly transcribed Ehrho/Ehrac genes and following flow cytometry analysis, we identified that silencing EhracM enhances dextran macropinocytosis and affects cellular migration persistence. Live imaging and interactome analysis unveiled the cytosolic and vesicular localization of EhRacM, along with its interaction with signaling and membrane traffic-related proteins, shedding light on EhRacM's multiple roles. Our findings provide insights into the specific regulatory mechanisms of macropinocytosis among endocytic pathways in E. histolytica, highlighting the significance of EhRacM in both macropinocytosis and cellular migration.